Financial distress/well-being and living situation in Ecuadorian health workers - Germán Lobos; Berta Schnettler; Carmen Lapo; María Núñez; Laura Vera (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
The tendency to live alone is a relatively recent phenomenon in Ecuador, but it is expanding rapidly. This study aims to identify factors associated with financial distress/well-being according to living situation (living alone vs. living with a partner) in Ecuadorian health workers. This study examined the construct of financial distress/well-being in a sample of 800 Ecuadorian health workers using cross-sectional data. Living situation was compared using generalized linear model analyses including income, age, children living at home, self-perception of health, depression, anxiety and stress, perceived social support, positive mental health, and hedonistic and austere profiles. Regarding financial well-being, workers living alone ranked lower and workers living with a partner ranked higher. In workers living alone the main sources of financial distress/well-being were income, children living at home, perceived social support, positive mental health, and hedonistic attitude towards indebtedness. In workers living with a partner the main sources of financial distress/well-being were income, age, self-perception of health, depression, anxiety and stress, perceived social support, positive mental health, and austere attitude towards indebtedness. Based on our results, we discuss potential public policy interventions that can be used to improve workers' financial well-being.